Learning with Wordwall: A Quasi-Experimental Study on Student Engagement and Learning Outcomes in Geography at a Senior High School in Indonesia - Alfira Dwi Oktavia; Muhammad Ansarullah S. Tabbu; Indrayani Simpuruh (Jurusan Teknik Informatika dan Komputer, 2025)
This study investigates the impact of Wordwall digital learning platform, on student engagement and learning outcomes in Geography studies at SMA Negeri 3 Maros. The objective was to evaluate how using interactive and gamified elements in Wordwall affects students' participation and academic performance. This study used a quasi-experimental method with a Nonequivalent Control Group Design, involving 62 students who were divided into two groups, namely an experimental group of 31 students and a control group of 31 students. The engagement data was collected through questionnaires, while the learning outcome data was obtained through pre-test and post-test. Data analysis was performed with normality test, homogeneity test, and Independent T-test. The results showed that the use of Wordwall increased student activeness with an average score of 90.39 in the experimental class, while the control class reached 88.29. Learning outcomes also showed a significant increase, with an average post-test score of 82.13 for the experimental class, while the control class was only 58.03. The statistical test shows a significance of 0.000, which proves the positive effect of using Wordwall media on student activeness and learning outcomes, so Wordwall is effective in improving Geography learning. The study contributes to the body of knowledge on using digital platforms in education and suggests further exploration of gamified learning tools in other subjects and educational settings.